2009
DOI: 10.1371/journal.pone.0005991
|View full text |Cite
|
Sign up to set email alerts
|

Melanopsin Bistability: A Fly's Eye Technology in the Human Retina

Abstract: In addition to rods and cones, the human retina contains light-sensitive ganglion cells that express melanopsin, a photopigment with signal transduction mechanisms similar to that of invertebrate rhabdomeric photopigments (IRP). Like fly rhodopsins, melanopsin acts as a dual-state photosensitive flip-flop in which light drives both phototransduction responses and chromophore photoregeneration that bestows independence from the retinoid cycle required by rods and cones to regenerate photoresponsiveness followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
172
2
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(193 citation statements)
references
References 41 publications
(136 reference statements)
16
172
2
3
Order By: Relevance
“…Under broadband natural or artificial light exposure, these two states exist in equilibrium. However, under monochromatic light exposure, it was shown that whereas especially short wavelengths initiated the phototransduction cascade (from R to M), long wavelengths could restore responsiveness by regeneration of the M to the R states (Melyan et al, 2005;Mure et al, 2009). The light intensities used in Mure et al's study to drive the M state back to the R state were quite high.…”
Section: Effects Of Artificial Dawn On Sleep Inertia 1233mentioning
confidence: 95%
“…Under broadband natural or artificial light exposure, these two states exist in equilibrium. However, under monochromatic light exposure, it was shown that whereas especially short wavelengths initiated the phototransduction cascade (from R to M), long wavelengths could restore responsiveness by regeneration of the M to the R states (Melyan et al, 2005;Mure et al, 2009). The light intensities used in Mure et al's study to drive the M state back to the R state were quite high.…”
Section: Effects Of Artificial Dawn On Sleep Inertia 1233mentioning
confidence: 95%
“…In contrast, melanopsin is a dual-state photopigment, in which photons drive both processes of phototransduction and part of chromophore regeneration (10)(11)(12). Recent rodent and human data suggest that exposure to longer wavelength light (590-620 nm; orange-red) triggers melanopsin chromophore regeneration and increases overall subsequent intrinsic photosensitivity of ipRGCs (13,14). Conversely, exposure to shorter wavelength light (∼480 nm; blue) favors phototransduction and decreases overall subsequent ipRGCs intrinsic photosensitivity (13,14).…”
mentioning
confidence: 99%
“…Recent rodent and human data suggest that exposure to longer wavelength light (590-620 nm; orange-red) triggers melanopsin chromophore regeneration and increases overall subsequent intrinsic photosensitivity of ipRGCs (13,14). Conversely, exposure to shorter wavelength light (∼480 nm; blue) favors phototransduction and decreases overall subsequent ipRGCs intrinsic photosensitivity (13,14). At the physiological level (12), the existence of two stable photon absorption states allows photoconversion of melanopsin between the 11-cis and all-trans isoforms of the photopigment-bound chromophore to drive both photic responses and restoration of light responsiveness (12,14), similar to processes of invertebrate rhabdomeric photopigments (15).…”
mentioning
confidence: 99%
“…Light-induced (i.e., photochemical) isomerization of PSB11 to its all-trans isomer (PSBAT) triggers an opsin conformational change that, ultimately, activates the receptor and signaling cascade (8,9). However, similar to invertebrate and in contrast to vertebrate rhodopsins, melanopsins are bistable (10). Indeed, although vertebrate rhodopsins need a retinoid cycle (11) to regenerate PSB11, melanopsins have an intrinsic light-driven chromophore regeneration function via PSBAT back-isomerization.…”
mentioning
confidence: 99%